Firing properties and microstructural characterization of porcelain stoneware from clay in Kimanis, Sabah - Sazmal Effendi Arshad (Universiti Malaysia Sabah, 2010)
Clay harbour great deal in industrial application of economy of Malaysia. In this study, the clay sample was taken from a known natural clay deposit at the area of Southwastern area of Sabah, Daingin in Kimanis and Inuman in Beaufort. The moisture content, pH, water absorption and linear shrinkage test were carried out to physicallycharacterize the clay. The outcome showed that the clay is porous and does not shrink at all. The clay were sieved to <125pm and flocculated in order to purify the clay sample 0from unwanted non-clay minerals. X-ray Fluorescence (XRF) analysis were performed on the flocculated sample. Si, Al, K and Fe were the elements which dominated the clay's chemical composition. X-ray Diffraction (XRD) analysis showed that kaolinite, quartz and illite were the dominant crystal phases present. The effect of firing on the phase evolution of the clay showed the decomposition of kaolinite and the growth of primary and secondary mullite. Batches containing the clay (50% and 70%), sodium feldspar and nepheline syenite (40% and 20%) and quartz (10%) were prepared based on dry pressing and fired over range of temperatures (900 to 1300°C). The microstructure of the batches containing different fluxes showed that the specimens contains primary and secondary mullite with presence of haematite. The different proportions of different clays used in the batches does not effect any of the presence of the crystalline phases. Quartz were seen to withstand the firing temperatures but as it goes higher, some quartz were seen to have melted. Both type of clay, Daingin and Inuman are suitable for industrial applications such as tiles production and pottery especially for production of porcelain stonewares based on the final microstructures achieved.